The impact of the livelihoods and income fortification and socio-civic transformation project on the quality of life, wellbeing, self-esteem, and quality of neighbourhood social environment among the youth in slum areas of in Kampala, Uganda - Andre M. N. Renzaho; Daniel Doh; Rashidul A. Mahumud; Moses Galukande; Joseph K. Kamara (BMC, 2020)
Abstract Background Various interventions to improve the quality of life (QoL) among slum dwellers across sub Saharan Africa have been implemented. However, the interventions impacts remain less understood. We assessed the impact of the Urban Program on Livelihoods and Income Fortification and Socio-civic Transformation (UPLIFT) project on QoL, psychological wellbeing, self-esteem, and the quality of neighbourhood social environment of young people aged 13-25 years in slum areas of Makindye and Nakawa Divisions in Kampala, Uganda. Methods The study was designed as a mixed method evaluation using repeated cross-sectional survey and grounded theory in both the intervention and comparison communities. The intervention effect was estimated using the difference-in-differences Kernel propensity-score matching technique, with bootstrapping. The "rcs" option was used given that data were from repeated cross-sectional surveys. A thematic analysis was adopted for the qualitative data to triangulate and complement the quantitative data. Results The UPLIFT project led to an improvement in QoL, psychological wellbeing, and self-esteem of young people. In terms of QoL, the project led to a six-percentage point increase in quality of living conditions scores (where higher scores reflect better living conditions; lower ones, worse living conditions). However, a negative effect was observed for personal independence whilst the project did not have any impact on social relations. In terms of self-esteem and psychological wellbeing, the project led to a 4.6-point increase in self-esteem scores, a 5.4-point increase in self-acceptance scores, a 5.3- point increase in purpose in life scores, a 5.7 - point increase in personal growth, and a 10.7-point increase in autonomy scores. However, the project had a negative effect on personal independence; and had no impact on environmental mastery and the quality of neighbourhood social environment. Conclusion Functional community-owned assets accumulation and capacity building initiatives for young people in slum areas improved their psychological wellbeing and quality of life. However, such initiatives do not appear to address social relationships and personal independence of young people in slum areas.